Rhetoric Ambiguity: A Pragmatic Study on Selected Poetic Excerpts - Salem, Rami Jamil (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aimed to investigate the rhetoric ambiguity which results from the semantic senses that morphologically similar words have and analyzes some selected poetic excerpts rhetorically and pragmatically. Methods: A descriptive-analytical approach was used to achieve the aim of the study; by applying the mechanisms of pragmatic theory to uncover the implicit meanings and the deep structure of poetry. Thus, the study analyzes these excerpts in light of the speech acts theory, the implicature theory, the conversational implicature, and contextuality. The study covers two frameworks: a theoretical one in which we define rhetoric ambiguity, and a procedural one in which some poetic examples are analyzed. Results: The findings indicated that pragmatics is very effective for analyzing the poetic examples, and for uncovering the implicit meanings and the deep structure of poetry, especially in the case of elliptical ambiguity. Moreover, metaphor types that encompass ambiguity differ according to the context. Finally, the study also found that there are rhetorical purposes and implicatures that are determined according to the speech acts in light of the rhetoric ambiguity. Conclusions: The study recommended carrying out more research about the field of Arabic rhetoric according to the data of new rhetoric (the argument theory). It also recommends casting light on the old rhetoric terms and involoves convincing objectives that make it possible to study and testify according to the argument and pragmatic theories